2017
DOI: 10.1098/rsif.2016.0761
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound imaging velocimetry with interleaved images for improved pulsatile arterial flow measurements: a new correction method, experimental and in vivo validation

Abstract: Blood velocity measurements are important in physiological science and clinical diagnosis. Doppler ultrasound is the most commonly used method but can only measure one velocity component. Ultrasound imaging velocimetry (UIV) is a promising technique capable of measuring two velocity components; however, there is a limit on the maximum velocity that can be measured with conventional hardware which results from the way images are acquired by sweeping the ultrasound beam across the field of view. Interleaved UIV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 49 publications
0
21
0
Order By: Relevance
“…The B-mode images were analyzed using a previously validated iterative PIV algorithm. 18,41 The algorithm consisted of two stages: First, a region of interest was selected in the LV outflow tract and a simple 2D crosscorrelation was applied on this region for all image pairs from 3 cardiac cycles. This cross-correlation was used to give a rough estimate for the velocity magnitude in that region, which also provided a periodic signal with the same periodicity as the cardiac cycle.…”
Section: Echo Pivmentioning
confidence: 99%
See 1 more Smart Citation
“…The B-mode images were analyzed using a previously validated iterative PIV algorithm. 18,41 The algorithm consisted of two stages: First, a region of interest was selected in the LV outflow tract and a simple 2D crosscorrelation was applied on this region for all image pairs from 3 cardiac cycles. This cross-correlation was used to give a rough estimate for the velocity magnitude in that region, which also provided a periodic signal with the same periodicity as the cardiac cycle.…”
Section: Echo Pivmentioning
confidence: 99%
“…Calibration of dimensions was based on the scaling factor (image resolution 800 by 600 pixels, spatial resolution 0.15-0.26 mm/px) in the DICOM data header. A sweep correction algorithm 18 was additionally applied to compensate for errors resulting from the echo-image creation by sweeping the echo beam through the imaging plane.…”
Section: Echo Pivmentioning
confidence: 99%
“…Zhou et al also predicted that for transient flows additional corrections are needed. Recently, Fraser et al (2016) showed that in pulsatile flow in a rabbit aorta this correction was indeed essential to obtain agreement with reference values. It is unclear whether the studies that do not mention the sweep effect perform a correction for it or not.…”
Section: Sweep Correctionmentioning
confidence: 99%
“…Studies of blood flow have been reported in rats ) and in rabbits Fraser et al 2016). So far these were primarily proof-of-principle experiments to show that the mean flow statistics match with reference (Doppler) data.…”
Section: Cardiovascular Flowsmentioning
confidence: 99%
See 1 more Smart Citation